Livelihood and Sustainability of Informal Waste Workers in Kathmandu Valley: A Qualitative Narrative Inquiry - Chaudhary, Govinda (Journal of Sustainability and Environmental Management, 2023)
Managing waste in growing urban cities is an increasing challenge day by day. Waste management is one of the basic essential services provided by local authorities and regulated bodies. Solid waste management includes collection, segregation, sorting, treatment, transportation, and final disposal. Along with the formal sector, the informal bodies are also active in Nepal. Informal waste workers are contributing to waste minimization and promoting environmental justice by involving in recycling activities. This study aimed to explore the five sustainable components (Human, Social, Physical, Financial, and Natural) of informal waste workers. The study was undertaken in the Kathmandu Valley by qualitative narrative inquiry. It was found that the income of informal waste workers varied, was unstructured, and was unpredictable. There is a need for the personal safety of waste workers to improve their quality of life. The study found that the workers are most vulnerable in terms of social capital, as they have poor relationships with their communities. It is important to incorporate them into the waste management system and acknowledge their contributions to the environment.